System for improvement of the QoE in public transportation - Neto, Bárbara Jael dos Santos (2020)
Due to the increase of the greenhouse effect and consequent climate changes, over the years, plans for reducing carbon emissions have been presented and discussed. One of the best ways for reducing and neutralizing carbon emissions is to use of collective transports, which is also one of the most accessible forms of contribution for the general public. However, it is not always simple or appealing. Therefore, one of the main goals of this work was to contribute in reducing the carbon emissions and to increase the sustainability of the urban areas. With that purpose in mind, a system that provides real-time information to the user was implemented, in order to encourage more people to use public transportation — and its impact was measured. The selected information was the following: real-time location of the bus, estimated time of arrival of the bus, route mapping, information about each stop. This information is presented to the user through dynamic signaling at main stops and internet services for computers and mobile phones. The developed work, in order to achieve the objectives mentioned, was to create a complete system of real-time information for public transportation in the Centro Region of Portugal, including a mobile app, a website and the backend for all the service and communications. The impact was measured by conducting surveys, presenting the project to the common population on an early state and, posteriorly, demonstrating and encouraging the use of the functional prototype.